EXPERIENCE WITH DOLUTEGRAVIR IN HIV PATIENTS AT A PUBLIC SECTOR HOSPITAL IN KARACHI, PAKISTAN: Dolutegravir in HIV - Batool, Farzana; Manzoor, Sohaima; Dhiloo, Azizullah Khan; Ismail, Humera Muhammad; Shaikh, Shah Muhammad; Baqi, Shehla (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the tolerability and efficacy of dolutegravir in naïve and experienced patients, their management and outcome.Study Design: Cross sectional study.Place and Duration of Study: Ruth KM Pfau Civil Hospital, Karachi Pakistan, from Apr 2018 to Apr 2020.Methodology: In this study all treatment-naïve and experienced HIV infected patients were included and started on integrase strand-transfer inhibitor dolutegravir (DTG) containing fixed dose combination at Sindh AIDS Control Program (SACP) was conducted. We documented virological suppression, defined as a viral load of